FUN DIVE AND UNDERWATER WELDING (SMAW): INTEGRATION OF EDUCATION, RECREATION, AND TECHNOLOGY IN THE UNDERWATER WORLD - Mulyawan, Hilman (Politeknik Kelautan dan Perikanan Karawang, 2026)
The sea has a dual role as a workspace as well as a recreation space. This study aims to describe two different activities that both take place below the surface of the water, namely underwater welding and fun diving. Underwater welding is an underwater welding technique used in the marine and construction industries, with challenges in the form of water pressure, low visibility, and electrical risks. Meanwhile, fun dive is a recreational diving activity that aims to enjoy the marine ecosystem, providing physical, mental, and environmental health benefits. The research method used is qualitative descriptive with data collection techniques through literature studies, observations, interviews, and documentation. The analysis was carried out thematically to identify the differences and linkages between the two activities. The results show that despite having different goals, both require diving skills and courage to face underwater conditions. Underwater welding contributes to the sustainability of marine infrastructure, while fun diving reinforces the value of recreation and environmental education. In conclusion, the ocean is not only a workspace for high-risk professions, but also a relaxing recreation space. The balance between the two emphasizes the importance of maintaining marine ecosystems so that they continue to function as industrial assets as well as a source of human happines